(3GdZQGeI GdeGdjI aj GdMOhO hGdLfGjGJ Ydi GdfaS GdHTQjI heGOhfgG aj Gdabg GdGSdGej (B/s - (3GdLejdj, eMSf YHO aQMGf UGdMs ((3HjQhJ(B: s (3OGQ GdcJH GdYdejI(B, s, 2006)
(3GMcGe GdZQGeI aj GdMOhO (B-(3GMcGe GdZQGeI aj GdSQbI (B-(3GMcGe GdZQGeI aj MO GdMQGHI (B-(3GMcGe GdZQGeI aj MO GdNeQ (B-(3GMcGe GdZQGeI aj MO GdbPa (B-(3GMcGe GdZQGeI aj LQjeJj GdHZj hGdQOI (B-(3GMcGe GdZQGeI aj GdLfGjGJ (B-(3GMcGe GdZQGeI aj GdLfGjI Yf GdfaS (B-(3GMcGe GdZQGeI aj GdLfGjI Yf eG Ohf GdfaSs
(3HHdjhZQGajG U(B.321-346 ((3GbJfGAGJ (B2014 3(3f(B)s
Keywords: (3GdLfGjGJs; (3GdZQGeGJ GdeGdjIs; (3Gdabg GdESdGejs